Some Factors Influencing the Prevalence of Gairdia lamblia and Entamoeba histolytica in a Sample of Patients in North of Baghdad - Al-Warid, Harith Sa'eed (Al-Nahrain Journal of Science, 2012)
Different factors were examined related with the prevalence of Giardia lamblia and Entamoeba histolytica infections in population live north of Baghdad which were (seasonal tendency, travelling history and source of drinking water) during the period April 2009 till the end of March 2010. The study revealed that the total rate of parasitic protozoan infection (G.lamblia and E. histolytica) was (15.33%) , the infectiion rate of G.lamblia was higher than the infection rate of E.histolytica as their rates were (11.66%) and (3.66%) respectively.There was high significant relation (p≤0.05) between infection rate of these parasites and both of drinking water and travelling status of the patient , high infection rate of (G.lamblia and E.histolytica) was observed in patients who drunk tab water and patients with travelling history,while the minimum infection rate was seen in patients who drunk the other types of drinking water (boiled, filtered and bottled) and patients with no travelling history.Finally the peak of Giardia and E.histolytica positive rates were seen in June 2009 (20%) and July 2009 (9.67%) respectively, while the minimum positive rate was seen in January 2010(1.85%) and November 2009 (1.61%) respectively. Statistical analysis using Person Correlation (r) illustrated that there was positively significant association (p≤0.05) between temperature and each of Giardia lamblia and E.histolytica infection, while there was significant negative association between number of rainfall per month and each of Giardia and E.histolytica infections.